The certainty-based directives and their argumentative role in the sermons of ahl Al-Bayt (peace be upon them) in the book Mizan Al-Hikmah by Muhammad al-Ray Shahri" - Al-Hamdani, Raba’a Hussein Mahdi; Harith, Mohammed Saleh Yaseen (Edelweiss Applied Science and Technology, 2024)
The one who contemplates the argumentative discourse of the Ahl al-Bayt (peace be upon them) sees a prominent appearance of certain directives in their argumentative discourse, including (the oath) in several structures, which affect the discourse and advance the process of directing and proving the utterances, due to the oath’s influential power on the recipient. The Imams of the Household (peace be upon them) used the style of restriction, which is considered one of the most important linguistic means that support the speaker in directing his speech and proving it to the recipient with certainty, and supports him in his argument, which makes the recipient go in the direction that the sender draws for him, under the pressure of the restrictive, performative structure of this style. The Imams of the Household (peace be upon them) often resort to using the restriction factor (innama) in employing their arguments and supporting their objectives; in order to remove any doubts or interpretations that may be stuck in the mind of the recipient, through what this factor possesses of a fixed and certain guiding power, so it confines and restricts these interpretations, and comes out with one result, which represents the goal of the speech. Verbs of certainty are considered to be among the directives with argumentative energy that influence the recipient, because these verbs carry meanings of assurance and certainty, which leave no room for doubt or hesitation in accepting the content of the speech. The people of the house included it(Peace be upon them)In their argumentative speech, with the aim of influencing the addressee and directing him in the direction they want.